2011
DOI: 10.1007/s00024-011-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

Summary of a 4-Year Fog Field Study in Northern Nanjing, Part 2: Fog Microphysics

Abstract: Comprehensive field observations of fog were conducted during the winters of 2006-2009 at the Nanjing University of Information Science & Technology, in order to study macro-and micro-physical structures and physical-chemical processes of dense fogs in northern Nanjing. The fog boundary-layer structures of different types and their corresponding characteristics are presented in Part I of these twin papers. In this second part, microphysical characteristics and droplet spectrum distributions of different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In terms of the spectral width characteristics of fog droplets, in the six fog processes, the spectral widths are at approximately 45 μm. It can be considered that the winter (strong) dense fog in Tianjin is a broad-spectrum fog based on suggestion of Niu et al [35].…”
Section: Measurement and Data Processingmentioning
confidence: 99%
“…In terms of the spectral width characteristics of fog droplets, in the six fog processes, the spectral widths are at approximately 45 μm. It can be considered that the winter (strong) dense fog in Tianjin is a broad-spectrum fog based on suggestion of Niu et al [35].…”
Section: Measurement and Data Processingmentioning
confidence: 99%
“…Usually measurements of droplet spectra reported in the literature were performed by single particle counters such as FSSP, CDP or FM-100 over the range µm. The corresponding droplet concentrations are in the range of a tenth to several hundred cm −3 (Wendisch et al, 1998;Garcıa-Garcıa et al, 2002;Gultepe and Milbrandt, 2007a;Niu et al, 2012;Price, 2011;Liu et al, 2011;Burnet et al, 2012;Lu et al, 2013;Zhao et al, 2013). In our cases, concentration values are rather low for semi-urban conditions with only one event exceeding 150 cm −3 .…”
Section: Impact Of Ccn Concentration On Fog Microstructurementioning
confidence: 44%
“…In our cases, concentration values are rather low for semi-urban conditions with only one event exceeding 150 cm −3 . For instance, Liu et al (2011) and Niu et al (2012) reported values recorded in Pancheng (China) as high as 800 and 1000 cm −3 , respectively. However we have shown that our resulting values of critical diameter are large with a median value of 3.8 µm.…”
Section: Impact Of Ccn Concentration On Fog Microstructurementioning
confidence: 99%
“…In our cases, concentration values are rather low for semi-urban conditions with only one event exceeding 150 cm −3 . For instance, Liu et al (2011) andNiu et al (2012) reported values 20 recorded in Pancheng (China) as high as 800 and 1000 cm −3 , respectively. However we have shown that our resulting values of critical diameter are large with a median value of 3.8 µm.…”
Section: Discussionmentioning
confidence: 99%
“…Usually measure-15 ments of droplet spectra reported in the literature were performed by single particle counters such as FSSP, CDP or FM-100 over the range µm. The corresponding droplet concentrations are in the range of a tenth to several hundred cm −3 (Wendisch et al, 1998;Garcıa-Garcıa et al, 2002;Gultepe and Milbrandt, 2007a;Niu et al, 2012;Price, 2011;Liu et al, 2011;Burnet et al, 2012;Lu et al, 2013;Zhao et al, 2013). In our cases, concentration values are rather low for semi-urban conditions with only one event exceeding 150 cm −3 .…”
Section: Discussionmentioning
confidence: 99%